Management of Product Recall in the Automobile Industry - Jia, Weihan (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2024)
A product recall occurs when products fail to meet certain safety standards or contain a defect that could cause serious harm to consumers. The objective of the thesis is to explore the sources of product recalls and the recall decision-making process. I test the proposed hypotheses in three related studies under the context of the US automobile industry. I propose novel complaint relevance and variety measures using text-based approaches to analyse the content of consumer complaints and product defects in recalls. The first two studies evaluate the impact of complaint relevance and complaint variety on the timing of recall decisions using a sample of 991 automotive recalls between 1993 and 2019. The third study examines the effect of chief executive officer (CEO) duality on the number of product recalls using a sample of 19 firms between 1994 and 2019. In the first study, I examine the impact of complaint relevance on the time taken to make a recall decision and how such an impact varies depending on product characteristics. The results show that consumer complaints with high relevance to product defects lead to a faster recall decision. Additionally, the impact of complaint relevance on time to recall is greater for a recall that involves various brands or that involves older car models. In the second study, I investigate the influence of complaint variety on time to recall and how such an influence is contingent on complaint related factors. The findings indicate that consumer complaints with ambiguous defect signals result in a slower recall decision. Moreover, the relationship between complaint variety and time to recall is stronger when consumer complaints describe a severer product defect or when consumer complaints are collected from diverse sources. The third study tests the relationship between CEO duality and the frequency of product recalls and the boundary conditions for such a relationship. The estimates of negative binomial models show that the existence of CEO duality decreases the frequency of product recalls. The effect of CEO duality on product recalls is greater for a firm with high firm liquidity or for a firm led by a CEO with prior CEO experience. Taken together, the thesis contributes to several streams of research in marketing, operations management, and strategic management.
APPROVED
Keywords: Time to recall; Customer complaint; Complaint relevance; Complaint variety; Econometric analysis; Textual analysis; Automotive industry; CEO duality; Upper echelons theory; Product recall